Recurrent urethral tumor with neuroendocrine differentiation in a female patient after radical cystectomy for bladder cancer - Yasuaki Murata; Toshiaki Shinojima; Yoko Nakahira; Mei Hamada; Atsushi Sasaki; Hirotaka Asakura (IJU Case Reports, 2023)
Introduction Urethral recurrence after radical cystectomy in female patients with bladder cancer is relatively uncommon. Recurrent bladder tumors with neuroendocrine differentiation are extremely rare. Case presentation A 71‐year‐old female patient who underwent radical cystectomy for bladder cancer presented with vaginal bleeding 19 months postoperatively. She was diagnosed with bladder cancer urethral recurrence. Urethral tumor en‐bloc resection with the anterior vaginal wall was performed by combining abdominal and vaginal approaches. Pathological examination revealed a recurrent tumor of urothelial bladder cancer containing small‐cell carcinoma components. Conclusion This case is the first report of a recurrent tumor with small‐cell carcinoma in the female urethra after radical cystectomy for pure urothelial carcinoma.